Common Eye Infections - Chaudhry, Imtiaz A. (IntechOpen, 2013)
Since ocular infections are one of the most frequent occurrences in ophthalmology, the treatment for these infections must be fast, precise and effective. In order to address this goal, it is important to identify and characterize the culprit microorganisms involved in the pathogenesis of ocular infections. Clinical diagnosis of ocular infections can be confirmed by several techniques based on microbiological test of ocular samples. Some of these techniques include classic microbiological testing in which it is necessary to isolate microorganisms to characterize them by biochemical analysis which require significant resources and timing.